76.6k views
2 votes
HELPPPPPPPPP 55 POINTS Isabel graphed the following system of equations.

2x – y = 6

y = -3x + 4



She came up with the solution (2,-2).

What were the 3 steps she did to get that solution?(Make sure they are in the correct order)

1)_______________________
2)_______________________
3)_______________________

HELPPPPPPPPP 55 POINTS Isabel graphed the following system of equations. 2x – y = 6 y-example-1
User Kickaha
by
5.6k points

1 Answer

3 votes

Answer:

1. Substitute y = -3x +4 for y in the first equation

2. Combine like terms and isolate x

3. Substitute in x into the 2nd equation to get y

Explanation:

1. Substitute y = -3x +4 for y in the first equation

2x- (-3x+4) = 6

2. Combine like terms

5x -4 = 6

5x -4 +4 = 6+4

5x=10 Divide by 5 to isolate x

5x/5 =10/5

x=2

3. Substitute in x into the 2nd equation to get y

y = -3x +4

y = -3(2) +4

y = -6+4

y=-2

(2,-2)

User Matthew Dalton
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.